Liver Transplantation in an Adult with Citrullinaemia Type 2 - Hui-Hui Tan; Wan-Cheng Chow; Kiat-Hon Lim; Wei-Keat Wan; Alexander Y. F. Chung; Peng-Chung Cheow; Chee-Kiat Tan (Journal of Transplantation)
Citrullinaemia is a urea cycle defect that results from a deficiency of the enzyme arginosuccinate synthetase. Type 1 disease is diagnosed in childhood, whereas Type 2 disease is adult onset. We report the outcome of a patient with citrullinemia Type 2 who received a liver transplant at our center and the implications of this diagnosis in liver transplantation.